The intense explosive activity of lava fountain sequences from Voragine crater at Etna volcano: new insights through high-precision borehole strain recordings - Bonaccorso, Alessandro; Carleo, Luigi; Currenti, Gilda; Sicali, Antonino (Frontiers in Earth Science, 2025)
Mount Etna is well known for its frequent lava fountains, or paroxysms, characterized by their intense explosive activity. Over the past decades, the Southeast Crater has been the most prolific, generating over a hundred events. More recently, three sequences of particularly powerful lava fountains were erupted from the Voragine Crater: four episodes between 3 and 5 December 2015, three between 18 and 21 May 2016, and six between 4 July and 15 August 2024. This intense eruptive activity, accompanied by significant ash dispersal and fallout, severely impacted the infrastructure and accessibility of eastern Sicily, causing disruptions to air services and the temporary closure of Catania’s international airport. In this study, we investigated these intriguing phenomena through the high-precision strain data recorded by Etna’s network of borehole dilatometers. We modelled and interpreted the source of these paroxysmal events, examining its position, the magnitude of its volumetric change during the paroxysms, and its relationship with the volcano’s plumbing system, thereby advancing our understanding of these dynamic processes.